INTEGRATED WEED MANAGEMENT IN DIRECT SEEDED RICE UNDER IRRIGATED CONDITION ( TED CONDITION (Oryza sativa L.) - UIKEY, NEETU; , R. K. TIWARI,; PUNIT TIWARI,; AMRITA TIWARI, (The Bioscan, 2018)
A field experiment was conducted in Kharif season of 2015 at, J.N.K.V.V. College of Agriculture, Instructional Farm, Rewa (M.P.) under All India Coordinated Rice Improvement Project to study- “Integrated Weed Management in Direct Seeded Rice under Irrigated Condition (Oryza sativa L.)”. The treatments comprised ten weed control methods which were laid out in randomized block design with three replications. The rice variety IR-64 was line sown under irrigated condition keeping seed rate 50 kg/ha and distances between rows 20 cm. The crop was grown as per recommended package of practices. The Study revealed that amongst the different weed control treatments, the equally highest grain yield (40.39 to 40.72q/ha) were obtained under pendimethalin + bispyribac sodium or 2,4-D (T2 and T3 ) and from butachlor + bispyribac sodium (T6 ) treatments. The highest weed control efficiency (78.12%)and net income (Rs. 38612 /ha) was achieved under T6 (Butachlor @1.5kg/ha(4DAS)+ bispyribac sodium @ 35g/ha (20DAS) followed by T2(pendimethalin@1.00kg/ha(4DAS)+bispyribac sodium @ 35g/ha (20DAS) 77.97% and Rs. 37.346/ha respectively